Дослідження жирно-кислотного складу фракцій подрібненого насіння льону - Ляшко, Галина Василівна; Тракало, Тетяна Олександрівна (My University, 2026)
У статті проаналізовано розподіл ліпідів у структурних частинах насіння льону, зокрема в зародку, ендоспермі та оболонці, що має значення для технологічних процесів переробки сировини та створення рецептур харчових продуктів. Показа-но, що найбільша концентрація жирів і поліненасичених жирних кислот зосереджена в зародковій частині насіння та становить 40—45%. Це зумовлює перспектив-ність використання продуктів переробки льону для створення функціональних харчових продуктів. Flaxseeds (Linum usitatissimum L.) represent a valuable oilseed crop widely used in the food industry and in dietary nutrition. Their high nutritional value is attributed to the significant content of lipids, proteins, dietary fiber, minerals, and various biologically active compounds. A key role in determining the nutritional and biological value of flaxseeds is played by polyunsaturated fatty acids, parti-cularly α-linolenic acid, which belongs to the omega-3 fatty acid group. This study examines the distribution of lipids within the structu-ral components of flaxseeds, including the embryo, endosperm, and seed coat, which is important for optimizing technological processes of raw material processing. The results demonstrate that the highest concentration of lipids and polyunsaturated fatty acids is localized in the embryo, accounting for approximately 40—45% of the total lipid content. These findings highlight the potential of flaxseed processing products for the development of functional food ingredients. The results confirm the relevance of further research on flaxseeds as a natural source of essential fatty acids and functional components in human nutrition. The incorporation of flaxseed raw materials into food technologies may contribute to enhancing the biological value of food products and promoting healthier dietary patterns. The experimental sample of flaxseeds contained a high amount of α-linolenic acid — 59%. Analysis of the fractions of ground flax-seeds showed that the highest content of fatty acids was observed in the 1.5 mm fraction. This can be explained by the fact that the em-bryo of flaxseeds is difficult to grind due to its high lipid content, particularly fatty acids, which give the embryo tissues plasticity and an oily consistency, thereby reducing the efficiency of mechanical grinding.
Keywords: кафедра технології зберігання і переробки зерна; жирокислотний склад; насіння; льон; олія; жир; омега-3; α-ліноленова кислота; функціональні продукти; fatty acid composition; seeds; flax; oil; fat; omega-3; α-linolenic acid; functional products